Faktor-Faktor yang Menentukan Minat Kewirausahaan Mahasiswa di Kampus Unisba Kota Bandung - Abi Abdillah; Ima Amaliah (Bandung Conference Series: Economics Studies, 2024)
Abstract. Although the number of job seekers in Indonesia increases from year to year, the number of jobs does not increase. The increasing number of job seekers is not balanced by the increasing number of job opportunities, thus contributing to the increasing unemployment rate in Indonesia. Therefore, entrepreneurship is a solution to create both formal and informal jobs. Students are one of the economic actors who are expected to contribute their thoughts and ideas to create many new jobs through entrepreneurial activities on campus. The purpose of this study was to identify the factors that determine the interest in entrepreneurship of Unisba students. The research method used is quantitative with a descriptive approach. Data were collected through. The analysis was carried out using descriptive statistical techniques to describe the characteristics of respondents and the factors that influence interest in entrepreneurship. The total number of students was 9,350 and a sample of 100 people was taken. The sampling technique was stratified random sampling. The Likert scale was used to measure the variables. Many determinants of self-efficacy, motivation, social relationships, physical facilities, institutions, culture, age, gender, education, capital, opportunities, etc. can be derived from the results of the data table. Compassion and empathy for others. Among these factors, the factor that determines Unisba students' interest in entrepreneurship is the factor of concern for others. Abstrak. Meskipun jumlah pencari kerja di Indonesia meningkat dari tahun ke tahun, namun jumlah lapangan kerja tidak bertambah. Meningkatnya jumlah pencari kerja tidak diimbangi dengan semakin besarnya kesempatan kerja, sehingga berkontribusi terhadap peningkatan angka pengangguran di Indonesia. Oleh karena itu, kewirausahaan merupakan solusi untuk menciptakan lapangan kerja baik formal maupun informal. Mahasiswa merupakan salah satu pelaku ekonomi yang diharapkan dapat menyumbangkan pemikiran dan gagasannya untuk menciptakan banyak lapangan kerja baru melalui kegiatan wirausaha di kampus. Tujuan penelitian ini adalah untuk mengidentifikasi faktor-faktor yang menentukan minat berwirausaha mahasiswa Unisba. Metode penelitian yang digunakan adalah kuantitatif dengan pendekatan deskriptif. Data dikumpulkan melalui. Analisis dilakukan dengan menggunakan teknik statistik deskriptif untuk menggambarkan karakteristik responden dan faktor-faktor yang mempengaruhi minat berwirausaha. Jumlah seluruh siswa adalah 9. 350 dan diambil sampelnya sebanyak 100 orang. Teknik pengambilan sampel adalah stratified random sampling. Skala likert digunakan untuk mengukur variabel. Banyak faktor penentu efikasi diri, motivasi, hubungan sosial, fasilitas fisik, institusi, budaya, usia, jenis kelamin, pendidikan, modal, peluang, dll dapat diturunkan dari hasil tabel data. Kasih sayang dan empati terhadap orang lain. Di antara faktor-faktor tersebut, faktor yang menentukan minat berwirausaha mahasiswa Unisba adalah faktor kepedulian terhadap sesama.